The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1074/jbc.m111.303958
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Phosphatase 1B (PTP1B) Deficiency Confers Resistance to Transforming Growth Factor-β (TGF-β)-induced Suppressor Effects in Hepatocytes

Abstract: Background: Tyrosine kinases and phosphatases modulate TGF-␤ signaling. Results: PTP1B deficiency attenuates TGF-␤-induced Smad phosphorylation correlating with suppression of growth inhibition and apoptosis, an effect that is reverted by genistein, and p65 or NOX1 knockdown. Conclusion: Lack of PTP1B impairs Smad activation in a NOX1 and NF-B-dependent manner. Significance: New insights are opened into the role of phosphatases in TGF-␤ signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…It has been reported that PTP1B participates in the development of fibrosis in liver (70) by activating hepatic stellate cells. PTP1B deficiency confers resistance to TGF-β through Smad inhibition in hepatocytes (57). Therefore, it would be worthwhile to further investigate the relationship among activation of α7 nAChR, PTP1B and TGF-β signaling in lung fibroblasts so that we can find novel therapeutic targets for combating lung fibrosis.…”
Section: Ly6cmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PTP1B participates in the development of fibrosis in liver (70) by activating hepatic stellate cells. PTP1B deficiency confers resistance to TGF-β through Smad inhibition in hepatocytes (57). Therefore, it would be worthwhile to further investigate the relationship among activation of α7 nAChR, PTP1B and TGF-β signaling in lung fibroblasts so that we can find novel therapeutic targets for combating lung fibrosis.…”
Section: Ly6cmentioning
confidence: 99%
“…The A549 cell line is frequently used in research regarding alveolar type II epithelial cells (52)(53)(54)(55). Therefore, The Regulatory Effect of `7 nAChR on TGF-a Signaling Depends on PTP1B It has been reported that PTP1B deficiency confers resistance to TGF-β through Smad inhibition in hepatocytes (57). We silenced Ptpn1 by infecting the fibroblasts with pLKO.1 shRNA-Ptpn1 lentivirus and repeated the experiment (shown in Figures 8-9) to clarify whether α7 nAChR regulates TGF-β signaling via PTP1B.…”
Section: Activation Of `7 Nachr Promotes Transcription Of Fibrotic Gementioning
confidence: 99%
“…Protection against Fasmediated apoptosis in the liver of PTP1B À/À mice correlated with an elevation and/or activation of numerous antiapoptotic signalling proteins including FLIPL, ERK1/2 and NF-kB. In addition, the resistance of PTPIB À/À hepatocytes to Fas-mediated apoptosis also required tyrosine kinase activity, because as occurred with TGF-b (Ortiz, 2012), PTP1B À/À hepatocytes were rendered susceptible to Fasmediated apoptosis by pre-treatment with genistein. Upon analysis of different PTP1B substrates, it was found that HGFR/Met showed sustained tyrosine phosphorylation and increased activation of its downstream mediator ERK1/2 in both livers and primary hepatocytes lacking PTP1B after Jo-2 treatment.…”
Section: Role Of Ptp1b In the Balance Between Cell Death And Survivalmentioning
confidence: 93%
“…The suppressor effects of this cytokine can be negatively regulated by activation of survival signals, mostly dependent on tyrosine kinase activity. Using immortalized hepatocytes, Ortiz et al (2012) have found that PTP1B deficiency conferred resistance against TGF-b mediated apoptosis and growth inhibition. At the molecular level, this effect correlated with lower Smad2/Smad3 phosphorylation and nuclear translocation, the lack of up-regulation of the inhibitory Smad7 and sustained activation of Akt and ERK1/2.…”
Section: Role Of Ptp1b In the Balance Between Cell Death And Survivalmentioning
confidence: 98%
“…Furthermore, VAS2870, a Nox inhibitor, decreased serum-dependent growth and phosphorylation of AKT and ERK and enhanced TGFβ-induced apoptosis in HCC cell lines (290). Nox1, which was co-elevated with Nox4 by HCV (71, 72), was also suggested to provide a partial resistance to hepatocyte apoptosis induced by TGFβ (290, 291), and excessive stimulation of the MAPK/ERK pathway produced similar effects (284). Furthermore, NS5A was recently found to interact with mixed lineage kinase 3 that activated p38 MAPK to combat apoptosis induced by sulfhydryl oxidizing agent, dithiodipyridine (292).…”
Section: Oxidative Stress and Pathogenesis Of Hccmentioning
confidence: 99%